2009
DOI: 10.1177/0734242x07085338
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin processing waste applied in the manufacturing of ceramic tiles and mullite bodies

Abstract: In the last few years, mineral extraction and processing industries have been identified as sources of environmental contamination and pollution. The kaolin processing industry around the world generates large amounts of waste materials. The present study evaluated the suitability of kaolin processing waste as an alternative source of ceramic raw material for the production of ceramic tiles and dense mullite bodies. Several formulations were prepared and sintered at different temperatures. The sintered samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…Thus, raw materials, natural or otherwise, with similar nature, which have similar roles and are capable of replacing each other, should be represented in the same vertex of such triangles (Correia, Dienstmann, Folgueras, & Segadães, 2009;Menezes et al, 2007Menezes et al, , 2008Menezes et al, , 2009. This explains the frequent use of the epithet "triaxial" to describe industrial ceramic products and suggests graphical representations based on triangles, usually equilateral.…”
Section: Analysis and Modeling Of Properties Of The Waste-based Firedmentioning
confidence: 99%
“…Thus, raw materials, natural or otherwise, with similar nature, which have similar roles and are capable of replacing each other, should be represented in the same vertex of such triangles (Correia, Dienstmann, Folgueras, & Segadães, 2009;Menezes et al, 2007Menezes et al, , 2008Menezes et al, , 2009. This explains the frequent use of the epithet "triaxial" to describe industrial ceramic products and suggests graphical representations based on triangles, usually equilateral.…”
Section: Analysis and Modeling Of Properties Of The Waste-based Firedmentioning
confidence: 99%
“…Particularly, the potential use of industrial wastes in ceramic processes has been widely investigated by various authors, demonstrating that products showing good technological properties could be obtained [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Nevertheless, just like at the end of its useful life and landfill deposition, compliance leaching tests are used to assess the environmental impact of the alternative product that incorporates the upgraded waste.…”
Section: Introductionmentioning
confidence: 99%
“…The mixture design of experiments (M-DoE) and the response surface (RS) methodologies are statistical tools that have been used to model and predict the technological properties of different ceramic products [12][13][23][24][25]. The basic assumption of the technique is that, when the process conditions are kept constant, the properties of the products (response variables) are solely determined by the proportion of the components in the mixture (input variables).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by our research group (Menezes et al, 2009a(Menezes et al, , 2009bBrasileiro et al 2006Brasileiro et al , 2008Santana et al, 2007) aimed at recycling the waste from the processing of kaolin, showed that the kaolin residue has high levels of SiO 2 and Al 2 O 3 , especially as a material of great potential for obtaining bodies that have properties for use in advanced ceramics, can be incorporated in ceramic formulations to obtain mullite.…”
Section: Using Kaolin Waste As Raw Materials For Obtaining Mullitementioning
confidence: 99%